Exploring Insights into Sustainability Assurance in the Chinese Context - Mu, Cong (Curtin University, 2024)
This thesis unveils the reasons for the stagnation in the Chinese sustainability assurance market. Based on forty interviews with sustainability report preparers and assurance providers, sustainability assurance quality is diagnosed at the level of stakeholders’ satisfaction rather than a problematic need to enhance sustainability reporting quality. The thesis adds a new theoretical framework based on framing theory to the literature. Additionally, indigenous Chinese sustainability characteristics and unique Chinese corporate governance structures emerge.